A Free‐standing electrochromic material of poly(5, 7‐bis(2‐(3, 4‐ethylenedioxy)thienyl)‐indole) and its application in electrochromic device. Issue 14 (29th April 2017) - Yang, Xiaoyan; Liu, Changlong; Guo, Jiabao; Wang, Ling; Nie, Guangming
ABSTRACT: Free‐standing poly(5, 7‐bis(2‐(3, 4‐ethylenedioxy)thienyl)‐indole) (PETI) was electrochemically obtained from 5, 7‐bis(2‐(3, 4‐ethylenedioxy)thienyl)‐indole (ETI) prepared by Stille coupling reaction of 5, 7‐dibromoindole and 3, 4‐ethylenedioxythiophene. For comparison, poly(5, 7‐bis(2‐thiophene)‐indole) was also electrosynthesized from 5, 7‐bis(2‐thiophene)‐indole (BTI) which was prepared from the 5, 7‐dibromoindole and thiophene. Characterizations of ETI and BTI were performed by cyclic voltammetry, scanning electron microscopy, 1 H NMR, and 13 C NMR spectroscopy. Spectroelectrochemical studies showed PETI had better electrochromic properties and showed two different colors (brown and blue‐violet) under various potentials with better maximum contrast (ΔT%) and coloration efficiency (CE). An electrochromic device (ECD) based on PETI and poly(3, 4‐ethylenedioxythiophene) (PEDOT) was also constructed and characterized. This ECD had fast response time, high CE, better optical memory, and long‐term stability. These results indicated that PETI had potential applications for ECD. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2356–2364 Abstract : Free‐standing poly(5, 7‐bis(2‐(3, 4‐ethylenedioxy)thienyl)‐indole) (PETI) was synthesized electrochemically in an acetonitrile solution. The polymer film shows reversible electrochemical processes and stable color change. Spectroelectrochemistry indicates that PETI has good electrochromic properties. The electrochromic device based on PETI and poly(3, 4‐ethylenedioxythiophene) is also fabricated and shows good electrochromic performance.